2016
DOI: 10.1007/s10815-016-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

An association between sperm PLCζ levels and varicocele?

Abstract: Purpose We aimed to compare the expression of phospholipase C ζ (PLCζ), as one of the main sperm factors involved in oocyte activation, at both RNA and protein levels in fertile men and those with varicocele. Methods This study included 35 individuals with male factor infertility presenting primary infertility with grade II and III unilateral varicocele and 20 fertile men without varicocele. Semen parameters were assessed according to WHO 2010. Sperm DNA fragmentation, relative expression of PLCζ at messenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
(59 reference statements)
0
14
0
2
Order By: Relevance
“…Consistent with that study, the percentage of sperm cells expressing PLCζ was significantly lower in our patients with OAT, indicating PLCζ impairment in these patients ( Figure 2B). Other studies have also demonstrated decreased expression and/or atypical localization of PLCζ in globozoospermic patients [25][26][27][28], patients with grade II and III varicocele [29], and patients with previous fertilization failure [16,25,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with that study, the percentage of sperm cells expressing PLCζ was significantly lower in our patients with OAT, indicating PLCζ impairment in these patients ( Figure 2B). Other studies have also demonstrated decreased expression and/or atypical localization of PLCζ in globozoospermic patients [25][26][27][28], patients with grade II and III varicocele [29], and patients with previous fertilization failure [16,25,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…SDF testing can serve as an ancillary test to conventional semen analysis in specific clinical scenarios. Evidence indicates that higher levels of SDF are observed in patients who are unable to conceive naturally [149,[273][274][275], who present with UMI/idiopathic infertility [185,188,[276][277][278][279][280][281][282], have RPL [116,138,[180][181][182][183][283][284][285][286][287][288][289][290][291][292][293][294][295], are diagnosed with varicocele [169][170][171][172][173][174][296][297][298][299][300][301][302][303][304]…”
Section: Strengthsmentioning
confidence: 99%
“…This is particularly concerning for PLCζ localisation patterns, where a dominant motif has yet to be isolated in relation to sperm health. To this degree, previous attempts to examine PLCζ profiles in human spermatozoa in relation to male conditions [24][25][26]28,[39][40][41][42] have been viewed with caution due to antibody specificity and protocol sensitivity. 30,43,44 Predictably, such shortcomings have led to conflicting results between the association of specific PLCζ localisation patterns and quantification levels.…”
Section: Successful Fertilisation Is Associated With Higher Total Lmentioning
confidence: 99%